Fatal hemangioblastoma: a case report and literature review - Zhang, Wenjie; Zhang, Xu; Ge, Chang; Yang, Cao; Li, Rui; Xu, Jingxuan (Frontiers in Oncology, 2026)
BackgroundHemangioblastoma (HB) is a benign tumor of the central nervous system (CNS), typically associated with a favorable prognosis following aggressive surgical resection. Spontaneous rupture and bleeding of these tumors are exceptionally rare, with only a small number of fatal cases reported. The rarity of such cases has impeded reliable epidemiological studies, underscoring the need to investigate the risk factors associated with HB-related mortality.Case ReportA patient presented with a 12-hour history of headache and rapidly became comatose approximately 30 minutes after admission. Neuroimaging revealed a large, solitary tumor located in the cerebellar vermis, medulla, and C1 segment of the spinal cord, with spontaneous rupture resulting in severe intracerebral hemorrhage. Despite emergency resuscitation and subsequent surgical resection, the patient unfortunately succumbed to their condition. Pathological examination confirmed the diagnosis of hemangioblastoma.ResultA review of studies published after 2000 identified 21 articles meeting the inclusion criteria, plus one additional case from our hospital, resulting in a total of 30 patients. A summary analysis was conducted on demographic information, age at first diagnosis, time to recurrence, overall survival, maximum tumor diameter, tumor locations (initial and recurrent), tumor texture, presence of VHL, surgical intervention, hemorrhage, cause of death, and embolization status. Missing data were excluded from the statistical analysis. The male-to-female ratio was 18:12, with a mean age at first diagnosis of 40.94 ± 13.44 years. Tumor diameters ranged from 1.6 cm to 5.2 cm, with a median of 3.3 cm. There were 3 cystic tumors, 10 solid tumors, and 2 cystic-solid tumors. Tumor origin sites included the cerebellum (18 cases), medulla (8 cases), and multiple locations (3 cases). Surgical resection was total in 24 cases, subtotal in 1 case, and embolization was performed in 4 cases; 23 cases did not undergo embolization. Seven patients (23%) died within one month, with causes of death including hemorrhage, tumor progression, infection, respiratory failure, and unspecified causes.ConclusionSpontaneous rupture and bleeding of hemangioblastomas are extremely rare, and there is currently insufficient evidence to establish clear treatment guidelines. While surgical resection is considered curative, patients with ruptured and bleeding tumors generally have a worse prognosis.AbbreviationsHB, Hemangioblastoma; VHL, von Hippel–Lindau; CNS, Central nervous system; OS, Overall survival time.